New Results of Normed Approach Space Via β-Approach Structure - Saeed, Shaimaa; Hussein , Boushra Y . (Iraqi Journal of Science, 2023)
Researchers have identified and defined β- approach normed space if some conditions are  satisfied. In this work, we show that every approach normed space is a normed space.However, the converse is not necessarily true by giving an example. In addition, we define β – normed Banach space, and some examples are given. We also solve some problems. We discuss a finite β-dimensional app-normed space is β-complete and consequent Banach app- space. We explain that every approach normed space is a metric space, but the converse is not true by giving an example. We define β-complete and give some examples and propositions. If we have two normed vector spaces, then we get two properties that are equivalent. We also explain that β-normed app- spaces are norm bounded with a condition. We show that functions of β-normed Banach spaces are β- contraction, with some results and properties. The sequentially β-contraction is also explained and  the relation between metric β- app- space and Hausdorff space is studied.